1997
DOI: 10.1520/jfs14211j
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shovel Trait on Carabelli's Trait in Taiwan Chinese and Aboriginal Populations

Abstract: Chinese and other Mongoloid populations differ from Caucasoids by having a high prevalence of shovel trait and a low prevalence of Carabelli's trait. This study was conducted to compare the association between the shovel and the Carabelli's traits between Chinese and aboriginal Mongoloid populations. The research is designed to sample randomly a Chinese population and an aboriginal population having low admixture with neighboring populations. The Mongoloid aboriginal group was from the Bunun tribe who resides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
3
11
1
Order By: Relevance
“…We found that the mesiodistal and buccolingual crown diameters of first molars were larger on average in those individuals who displayed Carabelli trait than in those who did not, a result consistent with many former studies (De Terra, 1905;Broekman, 1938;Keene, 1968;Sasaki, 1968;Lombardi, 1975;Noss et al, 1983;Hsu et al, 1997). Furthermore, cusp areas were larger in cuspal forms than in noncuspal forms, a trend that was particularly evident in the hypocone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the mesiodistal and buccolingual crown diameters of first molars were larger on average in those individuals who displayed Carabelli trait than in those who did not, a result consistent with many former studies (De Terra, 1905;Broekman, 1938;Keene, 1968;Sasaki, 1968;Lombardi, 1975;Noss et al, 1983;Hsu et al, 1997). Furthermore, cusp areas were larger in cuspal forms than in noncuspal forms, a trend that was particularly evident in the hypocone.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies included both metric and nonmetric data to make comparisons within and between populations, and some looked at the interactions or associations between these variables (Garn et al, 1966;Keene, 1968;Sasaki, 1968;Bang and Hasund, 1972;Lombardi, 1975;Noss et al, 1983;Reid et al, 1991Reid et al, , 1992Hsu et al, 1997). More recently, researchers began analyzing intracoronal components, e.g., cusp areas and intercuspal distances, which are thought to provide a better biological basis for describing tooth size variation (e.g., Biggerstaff, 1969;Corruccini, 1979;Townsend et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dimorphism in the expression of Carabelli's trait has been reported previously,[91923334053] but some authors found no significant difference in representation as observed in the present study. [21455455] Though there was no statistically significant difference, we observed that the expression of positive trait is more among males [28.6%] when compared to females [20.3%], in primary second molars.…”
Section: Discussionsupporting
confidence: 55%
“…[3233] Among the Caucasians, it is assumed that the Asiatic and Asiatic derived population show low trait frequencies, whereas, European population show high trait frequencies. [2735] Racial type of India seems to a complicated mixture of all major types.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] The determination of sex and ancestry can be assessed from skull shape and form. Generally, from skull appearance, forensic dentists can determine race within the three major groups: Caucasoid, Mongoloid and Negroid.…”
Section: Other Methods Of Dental Identificationmentioning
confidence: 99%